Problematika Hukum Shalat Gerhana Saat Tidak Tampak - Umam, Khotibul (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2022)
Abstract Eclipses are one of the rare natural phenomena. Apart from being a natural phenomenon, the appearance of an eclipse is the cause of the sunnah of the eclipse prayer. This phenomenon can be known by using contemporary methods of reckoning. To get to know more the author will discuss "Problematics of the Law of Eclipse Prayer When Invisible". The method used in this study is a qualitative type of library research. By understanding eclipses from an astronomical perspective, eclipses in the perspective of Islamic law, the types of eclipses, and the problems that are the reasons why it is sunnah or not to pray eclipses. Based on the results of the readings that the author did, there are several points, namely: astronomically, the eclipse phenomenon is defined as the closing of the observer's view of the celestial body by other celestial bodies that are closer to the observer caused by the value of astronomical longitude and the angle of inclination of the Moon's orbit around the Earth. A penumbral lunar eclipse is not a sunnah to khusuf prayer. When during an eclipse the weather is cloudy with thick clouds or heavy rain, then there are two opinions, namely: it is not sunnah to pray the eclipse "madzhab rukyah" and it is still sunnah to pray the eclipse "madzhab hisab".